RITUAL ISLAM DI TUGUREJO - Kholiq Nur Arifiana (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
As a religious geographic study, this paper presents about Islamtradition in Tugurejo Semarang. Nahdathul Ulama (NU) in Tugurejo as one of Islamic organisation is represented into three variants; traditional NU, modern NU and NUMAD (NU-Muhammadiyah). Meanwhile these groups do not have principle differences but they only have different belief in doing the ritual. This phenomena arises because of the fast growing of industrial development in Semarang.